The Evolution of Ogoh-Ogoh Performances in Fostering Religious Tolerance - Rahmadani, Anisya; Prasetyo, Kuncoro Bayu (Universitas Islam Negeri Madura, 2024)
The village of Linggoasri, located in Pekalongan Regency, is a village that features notable religious pluralism because its community consists of 13.02% Hindu, 86.83% Muslim, and 0.14% Buddhist. Although most of the population is Muslim, religious diversity does not hinder the recognition of the Ogoh-Ogoh tradition. Initially rooted in Hinduism, Ogoh-Ogoh has become a symbol of unity and diversity for all community members. The active participation of the community in the Ogoh-Ogoh celebration underscores the importance of this tradition as a cultural heritage recognized as belonging to all the people of Linggoasri Village. The research aims to explain the role of the Ogoh-Ogoh performance in fostering religious harmony and its impact on social integration in Linggoasri Village. Using a descriptive qualitative method, data were collected through participatory observation, interviews, and document studies. The research results show that the Ogoh-Ogoh parade plays a role in uniting the diverse religious community of Linggoasri. This event becomes a moment where all community members come together without concerning themselves with religious differences. The atmosphere of togetherness creates a point of integration that can open opportunities for interfaith dialogue and build mutual understanding among villagers, as well as being an effective medium for tolerance that teaches the values of appreciating diversity. From Bourdieu's habitus perspective, the Ogoh-Ogoh performance facilitates the formation of collective mindsets and behaviors. The active involvement of the Linggoasri community can deepen understanding of Hindu cultural values and appreciate religious diversity, thus forming an inclusive and equal society where respecting religious differences becomes a substantial value.